2011
DOI: 10.1038/eye.2011.335
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography changes before the development of choroidal neovascularization in second eyes of patients with bilateral wet macular degeneration

Abstract: Aim To describe the frequency of neovascular age-related macular degeneration (nAMD) in second eyes of patients undergoing ranibizumab therapy in their first eye and to evaluate the patterns of optical coherence tomography (OCT) abnormalities in fellow eyes before nAMD. Method Patients who developed choroidal neovascularization (CNV) in the second eye while on treatment for the first eye were identified. OCT scans of the second eyes, performed before the onset of CNV, were retrospectively examined and graded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…In this study, the most prevalent clinical finding was the presence of IRF and/or SRF imaged with OCT, and in 33% of patients, this was the only clinical indicator of nAMD in the second eye at baseline. Previous studies have shown that OCT fluid is a reliable marker of active nAMD [23] and OCT changes can be sudden and unpredictable [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the most prevalent clinical finding was the presence of IRF and/or SRF imaged with OCT, and in 33% of patients, this was the only clinical indicator of nAMD in the second eye at baseline. Previous studies have shown that OCT fluid is a reliable marker of active nAMD [23] and OCT changes can be sudden and unpredictable [24] .…”
Section: Discussionmentioning
confidence: 99%
“…AMD is a bilateral disease, and risk of neovascularization in a fellow eye increases over time after initial diagnosis [12]. Hence, it is important to determine the status of both eyes at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The common recommendation is, therefore, to monitor disease activity using SD-OCT, and on a monthly base. The concept of a ‘zero tolerance’ on OCT criteria is emerging, because of the rapid progression of exudative features and progressive loss of vision when initiation of treatment is delayed 61. However, persistent IRC should be considered signs of irreversible retinal degeneration and should not trigger further retreatment.…”
Section: Introductionmentioning
confidence: 99%